Hubungan berat badan dengan lingkar dada, tinggi gumba dan panjang badan pedet friesian holstein (hi)sampai umur 3 bulan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1993)
The objective of the study was to know the correlations of body weight to heart girth, body length and height at withers. Data were obtained from 12 Friesian Holstein calves consisted of 6 males and 6 females, from the first day to 3 months old. The data of body weight, hearth girth, body length, and height at withers were collected every two weeks, and were subjected to multiple correlation analysis. Correlation of body weight to heart girth, body length and height at withers (r = 0,96, Y = -85.938 + 0.90 X1 + 0.348 X2 + 0.379 X3) were very significant (P...rnKata kunci: Pedet, Friesan Holstein, Berat badan, Lingkar dada, tinggi gumba, panjang badan